RELIGIOUS VALUES BASED ON SPACE AND TIME IN COSMOLOGY PERSPECTIVE TO THE VERSE OF BADONG IN A FUNERAL CEREMONY OF TORAJANESE - Z. Zakaria (Universitas Sembilanbelas November Kolaka, 2018)
Ritual of badong is held in funeral ceremony of rambu solo in traditional belief of aluk to dolo/alukta in Toraja’s society, it was song and dance without music, and symbolic, verse of badong shown religious values of aluk to dolo/alukta. In data analysis, the study used descriptive qualitative and cosmology perspective in approaching the analysis. The aim of this study is want to know the relationship between being of universe and religious spirit of aluk to dolo/alukta which is stated in verse of badong in cosmology perspective. The result of the study is to find out the relationship between religious spirit of aluk to dolo/alukta in verse of badong and the space and time in orderliness of cosmos. They believed that after the death process, souls of the body will have a journey to reach a new place named puya, and the meaning of the death in belief of aluk to dolo/alukta is a way or transform the souls of the body from old world to the new world, puya is a village of soul of to dolo/tomembali puang (ancestors) authorized by Pong Lalondong, and puya in cosmology perspective was being at the west point of the earth.